Regulation PP2Ac methylation ameliorating autophagy dysfunction caused by Mn is associated with mTORC1/ULK1 pathway. (October 2021) - Xu, Yilu; Wei, Lancheng; Tang, Shen; Shi, Qianqian; Wu, Bin; Yang, Xiaobo; Zou, Yunfeng; Wang, Xinhang; Ao, Qingqing; Meng, Ling; Wei, Xuejing; Zhang, Ning; et al.
Abstract: Manganese (Mn) exposure leads to autophagy dysfunction and causes neurodegenerative diseases such as Parkinson's syndrome and Alzheimer's disease. However, the mechanism of neurotoxicity of Mn has been less clear. The methylation of the protein phosphatase 2A catalytic subunit determines the dephosphorylation activity of protein phosphatase and plays an important role in autophagy regulation. In this investigation, we established a model of Mn (0–2000 μmol/L) exposure to N2a cells for 12 h, used the PPME-1 inhibitor ABL-127, and constructed an LCMT1-overexpressing N2a cell line. We also regulated the PP2Ac methylation level and explored the effect of PP2Ac methylation on Mn-induced (0–1000 μmol/L) N2a cellular autophagy. Our results showed that Mn > 500 μmol/L induced N2a cell damage and increased oxidative stress. Moreover, Mn modulated autophagy in N2a cells by downregulating PP2Ac methylation, which regulated mTORC1 signaling pathway activation. Both ABL-127 and LCMT1 overexpression can upregulate PP2Ac methylation in parallel with ameliorating N2a cell abnormal autophagy induced by Mn, Briefly, the upregulation of PP2Ac methylation can ameliorate the autophagy disorder of N2a by Mn and effectively alleviate Mn-induced cytotoxicity and oxidative stress, indicating that regulation of autophagy is a protective strategy against Mn-induced neurotoxicity. Graphical abstract: Image 1 Highlights: Autophagy disruption is related to cytotoxicity caused by Mn in N2a cells. The down-regulation of PP2A methylation is involved in autophagy modulation by Mn. mTORC1/ULK1 activation is contributed to autophagy dysfunction. Regulation PP2Ac methylation ameliorating abnormal autophagy is associated with mTORC1/ULK1 pathway. Methylated PP2Ac decreases oxidative stress induced by Mn.